2018
DOI: 10.1128/aac.01620-17
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiviral Activity and Resistance Profile of the Next-Generation Hepatitis C Virus NS3/4A Protease Inhibitor Glecaprevir

Abstract: Glecaprevir (formerly ABT-493) is a novel hepatitis C virus (HCV) NS3/4A protease inhibitor (PI) with pangenotypic activity. It inhibited the enzymatic activity of purified NS3/4A proteases from HCV genotypes 1 to 6 in vitro (half-maximal [50%] inhibitory concentration = 3.5 to 11.3 nM) and the replication of stable HCV subgenomic replicons containing proteases from genotypes 1 to 6 (50% effective concentration [EC50] = 0.21 to 4.6 nM). Glecaprevir had a median EC50 of 0.30 nM (range, 0.05 to 3.8 nM) for HCV r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 42 publications
6
106
0
Order By: Relevance
“…This suggested that NS3P position 156 is the only position mediating major resistance to these PIs. In accordance with our findings, Ng et al reported that A156T selected under glecaprevir in the 1a(H77) subgenomic replicon resulted in high resistance and severe reduction in replication efficacy . However, fitness‐compensating substitutions were not identified and effects on viral assembly, as described in our study, cannot be studied in replicons.…”
Section: Discussionsupporting
confidence: 88%
“…This suggested that NS3P position 156 is the only position mediating major resistance to these PIs. In accordance with our findings, Ng et al reported that A156T selected under glecaprevir in the 1a(H77) subgenomic replicon resulted in high resistance and severe reduction in replication efficacy . However, fitness‐compensating substitutions were not identified and effects on viral assembly, as described in our study, cannot be studied in replicons.…”
Section: Discussionsupporting
confidence: 88%
“…Among these 67 patients with DAA treatment history, 58 (86.6%) were able to achieve SVR. The recently approved combination of glecaprevir, an NS3/4A inhibitor, and pibrentasvir, an NS5A inhibitor, have different resistance profiles than previous DAAs . Therefore, the combination of these drugs resulted in a high SVR rate for patients with prior DAA treatment failure in a phase 3 clinical trial conducted in Japan .…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies demonstrated antiviral activity of each drug component against each approved GT, with data generally demonstrating consistent activity across several representative subtypes of GT 4 and 6. Although it is not feasible to capture all of the genetic diversity of GT 4 and 6 subtypes in cell culture studies and clinical trials, antiviral activity generally has been demonstrated, at minimum, across the most common representative subtypes of GT 4 and 6…”
Section: Introductionmentioning
confidence: 99%